1959
DOI: 10.1002/1529-0131(195904)2:2<162::aid-art1780020208>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative distribution of proteins and glycoproteins of serum and synovial fluid

Abstract: The distribution of proteins and glyco-proteins in the synovial fluid and serum of normal patients and those with rheumatoid arthritis and other rheumatic diseases is presented. Joint disease tends to result in similar concentrations of protein in both serum and synovial fluid. Of particular interest is the distribution of alphaz glycoprotein. The relative concentration of this high molecular weight substance between serum and synovial fluid seems to be a most sensitive index of the semipermeability of the syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0

Year Published

1960
1960
1975
1975

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 14 publications
2
32
0
Order By: Relevance
“…Coulter (1962) noted the frequent alignment of cysternae or elongated endoplasmic reticulum parallel to the plasma membrane in these cells, and in the opinion of Kemp (1957) this arrangement is characteristic of a protein-producing cell. The nature of the protein secreted is a matter of some interest for it has been presumed for some time that the proteins in synovial fluid all originate from the plasma and that synovial cells play no role in their formation (Decker, McKenzie, McGuckin, and Slocumb, 1959;Hamerman and Schubert, 1962). However, further study (Sandson and Hamerman, 1962) demonstrated the presence in normal synovial fluid of a protein bound to a small percentage of the hyaluronate, and it was thought probable that this protein might participate in the synthesis of hyaluronate in the synovial membrane cells, or that the protein might be added to the hyaluronate at the cell wall and play a role in the passage of hyaluronate into synovial fluid.…”
Section: Functionsupporting
confidence: 63%
“…Coulter (1962) noted the frequent alignment of cysternae or elongated endoplasmic reticulum parallel to the plasma membrane in these cells, and in the opinion of Kemp (1957) this arrangement is characteristic of a protein-producing cell. The nature of the protein secreted is a matter of some interest for it has been presumed for some time that the proteins in synovial fluid all originate from the plasma and that synovial cells play no role in their formation (Decker, McKenzie, McGuckin, and Slocumb, 1959;Hamerman and Schubert, 1962). However, further study (Sandson and Hamerman, 1962) demonstrated the presence in normal synovial fluid of a protein bound to a small percentage of the hyaluronate, and it was thought probable that this protein might participate in the synthesis of hyaluronate in the synovial membrane cells, or that the protein might be added to the hyaluronate at the cell wall and play a role in the passage of hyaluronate into synovial fluid.…”
Section: Functionsupporting
confidence: 63%
“…Serum antibodies and blood clotting factors are either absent or present only in small concentrations in normal synovial fluid (27). Minor degrees of inflammation, as in osteoarthritis or traumatic arthritis, change this selective permeability (28)(29)(30). The protein concentration rises, and greater amounts of globulin can be found in synovial fluid.…”
Section: Resultsmentioning
confidence: 99%
“…The concentration of a serum protein in synovial fluid depends upon its concentration in the serum and the degree of synovial permeability present (23,24) except when local synthesis or destruction occurs. Hedberg (4) showed a high correlation between complement and total protein in synovial fluids of patients with degenerative joint disease when these values were corrected for serum levels by employing the SF/S values.…”
Section: Methodsmentioning
confidence: 99%